Helicase-like transcription factor-deletion from the tumor microenvironment in a cell line-derived xenograft model of colorectal cancer reprogrammed the human transcriptome-S-nitroso-proteome to promote inflammation and redirect metastasis - Helmer, Rebecca A. (PLoS One, 2021)
Methylation of the HLTF gene in colorectal cancer (CRC) cells occurs more frequently in men than women. Progressive epigenetic silencing of HLTF in tumor cells is accompanied by negligible expression in the tumor microenvironment (TME). Cell line-derived xenografts (CDX) were established in control (Hltf(+/+)) and Hltf-deleted male Rag2(-/-)IL2rg(-/-) mice by direct orthotopic cell microinjection (OCMI) of HLTF(+/+)HCT116 Red-FLuc cells into the submucosa of the cecum. Combinatorial induction of IL6 and S100A8/A9 in the Hltf-deleted TME with ICAM-1 and IL8 in the primary tumor activated a positive feedback loop. The proinflammatory niche produced a major shift in CDX metastasis to peritoneal dissemination compared to controls. Inducible nitric oxide (iNOS) gene expression and transactivation of the iNOS-S100A8/A9 signaling complex in Hltf-deleted TME reprogrammed the human S-nitroso-proteome. POTEE, TRIM52 and UN45B were S-nitrosylated on the conserved I/L-X-C-X(2)-D/E motif indicative of iNOS-S100A8/A9-mediated S-nitrosylation. 2D-DIGE and protein identification by MALDI-TOF/TOF mass spectrometry authenticated S-nitrosylation of 53 individual cysteines in half-site motifs (I/L-X-C or C-X-X-D/E) in CDX tumors. POTEE in CDX tumors is both a general S-nitrosylation target and an iNOS-S100A8/A9 site-specific (Cys(638)) target in the Hltf-deleted TME. REL is an example of convergence of transcriptomic-S-nitroso-proteomic signaling. The gene is transcriptionally activated in CDX tumors with an Hltf-deleted TME, and REL-SNO (Cys(143)) was found in primary CDX tumors and all metastatic sites. Primary CDX tumors from Hltf-deleted TME shared 60% of their S-nitroso-proteome with all metastatic sites. Forty percent of SNO-proteins from primary CDX tumors were variably expressed at metastatic sites. Global S-nitrosylation of proteins in pathways related to cytoskeleton and motility was strongly implicated in the metastatic dissemination of CDX tumors. Hltf-deletion from the TME played a major role in the pathogenesis of inflammation and linked protein S-nitrosylation in primary CDX tumors with spatiotemporal continuity in metastatic progression when the tumor cells expressed HLTF.